APPLICATION OF A STRONG ACID RESIN AS ION EXCHANGE MATERIAL FOR WATER SOFTENING – EQUILIBRIUM AND THERMODYNAMIC ANALYSIS - BOGDAN BANDRABUR; RAMONA-ELENA TATARU-FĂRMUŞ; LILIANA LAZĂR; GHEORGHE GUTT (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The adsorption equilibrium isotherm of calcium from aqueous solution onto Purolite C100E synthetic ion exchange resin have been studied and modelled. The batch method has been employed, using Ca2+ concentration in calcium chloride solution ranging from 42 to 176 mg•L-1 at pH 7.1. The suitability of the Langmuir and Freundlich adsorption isotherm was investigated for calcium chloride solutions – ion exchange resin system. The temperature effect on the calcium removal onto resin was also investigated, and various thermodynamic parameters (ΔG, ΔH and ΔS) have been calculated. These parameters indicate the spontaneous and endothermic nature of the ion exchange process.